Metabolic Reprogramming and Molecular Rewiring in Cancer: Therapeutic Opportunities - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: A lot of contemporary cancer research has concentrated on genetic influence. However, cancer also involves biochemical changes, such as metabolic adaptation to support the aberrant cell proliferation.CONTENT: The fast cell proliferation in cancer cells enforce a metabolic re-arrangement to promote their long-term survival. The increased glucose uptake and fermentation of glucose to lactate are common features of this altered metabolism known as “the Warburg effect”. These metabolic pathways regulation enable cancer cells to produce adenosine triphosphate (ATP) in an efficient way. Epigenetic and metabolic changes also both affect molecular rewiring in cancer cells and promote cancer development and progression.SUMMARY: Metabolic rewiring and epigenetic remodeling establishing a direct link between metabolism and nuclear transcription to promote the survival of tumor cells. A further understanding of how metabolic remodeling can result in epigenetic changes in tumors, affecting cancer cell differentiation, proliferation, and/or apoptosis, will lead to a new strategy for cancer therapy.KEYWORDS: cancer metabolism, epigenetics, metabolic reprogramming, molecular rewiring